2019
DOI: 10.1016/j.porgcoat.2019.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic, corrosion protection and adhesion properties of acrylic nanocomposite coating containing silane treated nano zinc oxide: A combined experimental and simulation study

Abstract: TitlePhotocatalytic, corrosion protection and adhesion properties of acrylic nanocomposite coating containing silane treated nano zinc oxide: a combined experimental and simulation study Short title Photocatalytic, corrosion protection and adhesion properties of acrylic nanocomposite Article typeResearch Paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The microbiologic studies demonstrated that yeast cells deposited in a glass surface exposed to 15 minutes of UV light (254nm) reached a 34% inhibition growth, and yeast cells on a SnO2 thin film, exposed to the same amount of UV radiation reached a 66% growth inhibition, results that were expected according to SnO2 photocatalytic activity reported in the scientific literature [2,5,6]. A comparison between yeast cells deposited on SnO2 thin films, with and without exposure to UV light, is shown in Figure 2c-d…”
Section: Figure 1amentioning
confidence: 84%
See 1 more Smart Citation
“…The microbiologic studies demonstrated that yeast cells deposited in a glass surface exposed to 15 minutes of UV light (254nm) reached a 34% inhibition growth, and yeast cells on a SnO2 thin film, exposed to the same amount of UV radiation reached a 66% growth inhibition, results that were expected according to SnO2 photocatalytic activity reported in the scientific literature [2,5,6]. A comparison between yeast cells deposited on SnO2 thin films, with and without exposure to UV light, is shown in Figure 2c-d…”
Section: Figure 1amentioning
confidence: 84%
“…UV light has been used for decades as a very efficient wide range antimicrobial method, and resistance mechanisms had not been an important factor that could affect disinfection performance. Certain metal oxides, like SnO2 have photocatalytic properties that allow them to increase the efficacy of UV light antimicrobial activity [5][6][7]. In the present work antibacterial testing was performed employing SnO2 substrate coupled with UV light to measure the ensemble activity against C. albicans a common pathogen in the hospital environment from the microbiologic and scanning electron microscopy perspective.…”
Section: Introductionmentioning
confidence: 99%
“…However, most published works only focused on the micro-sized ZnO particles, with a very limited photocatalytic behavior in the coating system. In the case of the nanocomposite coating, their antimicrobial activity and self-cleaning ability could be achieved, with nano-ZnO being the most promising and effective photocatalyst [ 18 , 19 , 20 , 21 ]. As reported, after absorbing UV radiation, an electron of ZnO at the valence band jumps into the conduction band, creating an h + hole [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rate of formation of ferric oxide compounds purely depends on the preexisting holes available for the electrolyte percolation. If these corrosive pore domains are coated with the heterogeneous rough atoms like nitrogen or silica, the rate of ferrous oxide production will be highly reduced [15]. In accordance with the increase of printed circuit board powder in the mixture, the corrosion resistance efficiency of the coating increases.…”
Section: Potentio-dynamic Polarizationmentioning
confidence: 99%